REVIEW ARTICLE: METODE UJI TEGANGAN PERMUKAAN DALAM ZAT CAIR - Ika Lismayani Ilyas; Retno Wahyuningrum; Ines Septiani Pratiwi; Riska Asmayanti; Murni; Nur Nisawati; Hasyim Asyari; Aulia Alfia; Putri Astin; Arianto; Nopianti Sa’dan; Hikma; Regina Tri Olivia Marundu; Resky Rahayu Ningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Surface tension is an important physicochemical property that plays a major role in determining the interfacial behavior of a liquid in various scientific and industrial applications. Accurate surface tension measurement is required to understand liquid interactions, optimize formulation processes, and predict the stability of dispersed systems such as emulsions. This review article examines and compares several commonly used methods in surface tension measurement, namely the capillary rise method, the Du Noüy ring method, the drop and drop–weight/volume comparison method, the maximum bubble pressure method (MBPM), and micro-droplet measurement using Atomic Force Microscopy (AFM). Each method is analyzed based on its working principle, level of accuracy, advantages, limitations, and suitability for various types of liquids. The results of the review show that classical methods such as Du Noüy and the stalagmometer remain relevant because they are practical and easy to use, while modern methods such as AFM offer high sensitivity for micro-droplet samples. Overall, selecting the appropriate measurement method must consider sample characteristics, instrument availability, and analytical objectives. This review is expected to serve as a comprehensive reference for researchers, students, and industry practitioners in determining the most suitable technique for surface tension measurement.